Numerical study on nonlinear growth of m/n = 3/1 double tearing mode in high Lundquist number regime. (30th May 2019) - Guo, W; Ma, J; Yu, Q
Abstract: The nonlinear growth of the m / n = 3/1 double tearing mode (DTM) is numerically investigated in cylinder geometry with non-monotonic radial profiles of the equilibrium safety factor, having two q = 3 surfaces. The formation of plasmoids is found in high Lundquist number regime in such configurations for the first time. During the nonlinear growth of DTM, long and thin Sweet–Parker current sheets are formed near the original inner and outer rational surfaces and become tearing unstable for a large enough Lundquist number, leading to secondary and tertiary magnetic islands which accelerate the magnetic reconnection. The plasmoids also affect the magnetic topology at nonlinear mode saturation. The system can eventually saturate at a quasi-stationary state with small island pairs. The simulation results show that the Lundquist number and the distance between two rational surfaces have important effects on plasmoids formation.